2018
DOI: 10.3390/technologies6010020
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Blended Waste Materials in Bricks

Abstract: Cement is considered a key raw material for brick production. However, excessive use of cement leads to a negative environment impact. Cement replaced with locally available waste materials has a significant potential to address this environmental impact, especially in the construction industry by contributing to cleaner production. The objective of this research is to investigate the performance of brick where cement is replaced by fly ash and palm oil fuel ash, waste materials typically available in Malaysia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 32 publications
(44 reference statements)
0
20
0
1
Order By: Relevance
“…The first pertains to the narrow scope associated with the review papers compared to the comprehensive examination undertaken in this research. The review of Rahman et al [13][14][15][16] shows that the researchers focus on the sustainable development of bricks [16], masonry blocks [15], and self-compacting concrete [13]. In contrast, this review examines a broad range of construction materials, including brick/masonry elements, green concrete, insulation materials for buildings, reinforcement materials for buildings, particleboards, and bio-based plastics.…”
Section: Novelty Of the Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…The first pertains to the narrow scope associated with the review papers compared to the comprehensive examination undertaken in this research. The review of Rahman et al [13][14][15][16] shows that the researchers focus on the sustainable development of bricks [16], masonry blocks [15], and self-compacting concrete [13]. In contrast, this review examines a broad range of construction materials, including brick/masonry elements, green concrete, insulation materials for buildings, reinforcement materials for buildings, particleboards, and bio-based plastics.…”
Section: Novelty Of the Researchmentioning
confidence: 99%
“…Secondly, Rahman et al [16] observed that there lacked adequate guidelines to facilitate the incorporation of waste materials during the development of bricks. Nevertheless, the findings obtained showed that fly ash bricks improved significantly after adding 10% palm oil fuel ash (POFA), while the highest compressive strength value was also obtained when fly ash and POFA were added at a ratio of 1:1.…”
Section: Novelty Of the Researchmentioning
confidence: 99%
“…In Western Europe, solid fuels -fuel briquettes and pellets (granular fuel) -have become widespread [28][29][30][31][32]. The calorific value of such material made from vegetable waste is comparable to coal, and its relative cheapness allows it to be used as industrial energy sources and for domestic purposes [2,11,19].…”
Section: Materials Methods and Objects Of Researchmentioning
confidence: 99%
“…Rahman et al [12] investigated the performance of bricks using fly ash and palm oil fuel ash instead of cement. Their test results revealed that according to the Malaysian standard MS76:1972, both fly-ash-incorporated and palm-oil-fuel-ash-incorporated bricks satisfied Class 1 and Class 2 load-bearing brick requirements, as well as ASTM's water absorption requirements C55-11.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the factors affecting the performance of fired bricks include raw material composition and firing conditions [1,[7][8][9][10][11][12]27]. In a factorial design, as the design parameters or parameter levels increase, not only do the time and cost of the experiment increase significantly, but the experimental conditions become more complicated.…”
Section: Introductionmentioning
confidence: 99%